Selection of Police Personnel: A Case Study of Slovenia - Mogyoródi, Gergely (Magyar Rendészet, 2019)
This paper presents the selection procedure (the entry requirements and eligibility criteria) and in this perspective, the organisational and educational characteristics of the Slovenian police. The aim is to present the results of research conducted in international environment and to compare its unique characteristics with the Hungarian practice.